Improvement in semen parameters after varicocoelectomy - Kumar, Sandeep; Singh, Sakshi (International Surgery Journal, 2020)
Background: Varicoceles are associated with abnormal sperm parameters. The difference is more marked in cases with infertility and higher grades of varicocele. Following ligation of varicocele, there is a significant improvement in the sperm counts. Methods: The study was conducted in the department of general surgery at Maulana Azad Medical College and associated Lok Nayak Hospital from September 2012 to April 2014. The study was conducted on 40 numbers of patients. These were divided into 2 groups, group 1 (n=20) constituted of patients with varicocele who are symptomatic. Group 2 (n=20) constituted of patients with varicocele who are asymptomatic (infertile). All patients were evaluated by clinical examination and Doppler to grade the varicocele. All patients underwent detailed semen analysis. Patients of both the groups underwent FNAC of bilateral testes. The patients with clinical or Doppler detectable varicocele were taken up for low ligation of varicocele. Patients were followed up and all above parameters were repeated about 3 months after surgery. Results: The sperm morphology, counts and motility increase significantly in group 2 patients and sperm counts and morphology increased significantly in group 1 while motility not increased significantly. Conclusions: Most of the patients who presented to us were in the age group of 25-35 years. Longer duration of disease in patient with infertility is also suggestive of the fact that varicocele is a progressive disease and leads to testicular dysfunction over time leading to infertility. Most of the varicoceles were either left sided or bilateral